THE PAIN THAT TRAVELS: A COMPREHENSIVE REVIEW OF REFERRED PAIN - Asatullyev Rustam Baxtiyorovich,; Asherbekova Rayhon Kalilbek qizi, (TADQIQOTLAR, 2026)
Abstract: Referred pain is a fascinating and clinically significant phenomenon in which pain is perceived at a location distant from its actual source of origin. This neurophysiological  phenomenon  poses  a  substantial  diagnostic  challenge  for clinicians,  as  the  site  of  discomfort  often  does  not  correspond  to  the  underlying pathological process. Common examples include cardiac ischemia presenting as left shoulder or jaw pain (angina pectoris), diaphragmatic irritation causing shoulder tip pain,  and  lumbar  disc  herniation  producing  sciatic  pain  radiating  down  the  lower extremity. This article provides a systematic review of the historical understanding, neuroanatomical  basis,  and  leading  theories  of  referred  pain,  including  the convergence-projection  theory,  the  facilitation  theory,  and  the  axonal  branching theory.  The  clinical  relevance  of  referred  pain  is  explored  across  multiple  medical specialties,  including  cardiology,  gastroenterology,  pulmonology,  orthopedics,  and neurology. The article also discusses diagnostic approaches, including the use of local anesthetic  blocks  and  imaging,  and  outlines  management  strategies.  The  review concludes with a discussion of the clinical red flags (e.g., sinister causes of referred pain  such  as  aortic  dissection  or  pancreatic  cancer)  and  future  research  directions, including central sensitization and neuroimaging studies.